Study on the Influence of Water Content on the Shear Behavior of the Soil–Structure Interface Under a Temperature Field - Jian Chen; Hao Jiang; Yongde Liu; Yanting Wu; Xuan Zhang; Weidong Pan (Buildings)
Energy piles are highly favored for their excellent, low energy consumption in providing heating for public residences. The temperature field changes the activity of the diffuse double electric layer (DEL) on the particle surface, thereby altering the distribution of the stress field in the soil and ultimately affecting the mechanical properties of the interface between the energy pile and the soil. Therefore, studying the influence of water content on the mechanical behavior of the soil–structure interface in the temperature field is crucial for energy pile safety. This study used a modified temperature-controlled direct shear apparatus to obtain the influence of water content and temperature on the shear behavior of the soil–structure interface. Then, the test results were analyzed and discussed. Finally, three results were obtained: (1) The water content of bentonite (wbent) had a significant impact on the shear stress–shear displacement curve of the soil–structure interface; when the wbent was less than the wp of the bentonite, the τ-l curve exhibited a softening response, then displayed a hardening response. (2) The shear strength of the soil–structure interface gradually decreased with the increase of wbent. (3) The shear strength of the soil–structure interface increased with increasing temperature under various wbent and vertical loads.